Design, optimization and experimental characterization of RF injectors for high brightness electron beams and plasma acceleration. (1st December 2022) - Shpakov, V.; Alesini, D.; Anania, M.P.; Behtouei, M.; Buonomo, B.; Bellaveglia, M.; Biagioni, A.; Cardelli, F.; Carillo, M.; Chiadroni, E.; Cianchi, A.; Costa, G.; et al.
Abstract: In this article, we share our experience related to the new photo-injector commissioning at the SPARC_LAB test facility. The new photo-injector was installed into an existing machine and our goal was not only to improve the final beam parameters themselves but to improve the machine handling in day-to-day operations as well. Thus, besides the pure beam characterization, this article contains information about the improvements, that were introduced into the new photo-injector design from the machine maintenance point of view, and the benefits, that we gained by using the new technique to assemble the gun itself.